Endovascular Repair of a Large Profunda Femoris Artery Pseudoaneurysm - Ahsan Syed Khalid; Omar M. Ghanem; Seyed Mojtaba Gashti (Case Reports in Vascular Medicine)
Profunda femoris artery aneurysms and pseudoaneurysms are a rare cause of peripheral arterial aneurysms but their risk of rupture is quite high. We have presented a case of a left lower leg pseudoaneurysm. We have shown that endovascular repair with angioplasty and stenting is a suitable treatment method for such a pseudoaneurysm. Due to the limited data on this disease, we suggest multi-institute collaboration to identify and standardize management for the treatment.